Pemberian Sosialisasi dan Pemeriksaan Kesehatan Bagi Lansia di Panti Sosial Tresna Werdha Wana Seraya - Putri, Putu Cahya; Cahya Dewi, Ni Kadek Arika; Diah Arthari, Ni Kadek Ayu; Suasnawa, I Gede; Sutrisna, Ni Nyoman Dwi; Suandari, Putu Vierda Lya; Nugraha, I Nyoman Adikarya (Jurnal Abdimas Jatibara, 2025)
Health check-up activities for the elderly at the Wana Seraya Wredha Social Home are a form of community service that aims to improve the quality of life of the residents of the home. The elderly are a vulnerable age group and require routine health monitoring to prevent and detect chronic diseases and other health problems early. This community service activity was carried out by the Hospital Administration Student Association in collaboration with the Medical Laboratory Technology Student Association which included blood sugar and uric acid examinations. The results of the activity showed that several elderly people experienced uric acid and blood sugar levels that exceeded normal limits, this can educate the elderly about the need for better health management. This activity received a positive response from residents and managers of the home, and was considered useful in increasing awareness and knowledge of the elderly about their health. By holding this health check-up, it is hoped that it can monitor the health conditions of the elderly so that it can improve their overall quality of life.